Colorectal cancer as a complex adaptive system: integrating the hallmarks of cancer with complexity theory - Basbus, Luis R. (Frontiers in Oncology, 2026)
The paradigm of the Hallmarks of Cancer, updated by Douglas Hanahan in 2022, represents one of the most influential syntheses for understanding the functional capabilities that sustain neoplastic transformation. However, its traditional interpretation, often reductionist and fragmentary, does not capture the non-linear, emergent, and adaptive dynamics of tumor behavior. This review proposes a reinterpretation of the hallmarks through the lens of complexity theory, conceptualizing colorectal cancer (CRC) as a self-organizing, open system operating far from equilibrium. Using an integrative conceptual approach, we map the ten classical hallmarks and the new dimensions proposed in 2022 (phenotypic plasticity, non-mutational epigenetic reprogramming, polymorphic microbiomes, and senescence) onto the fundamental properties of complex systems: nonlinearity, emergence, feedback, openness, and historical dependence. We argue that CRC should not be understood as a simple sum of molecular alterations but as a dynamic network of interactions among cells, tissues, and microenvironments where global organization emerges from local rules. This systems-based perspective provides a conceptual foundation for translational models and integrative methodologies in oncology.